2009
DOI: 10.1210/jc.2008-2325
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Longevity Is Associated with Increased Serum Thyrotropin

Abstract: The TSH population shifts to higher concentrations with age appear to be a continuum that extends even to people with exceptional longevity. The inverse correlation between TSH and FT4 in our populations suggests that changes in negative feedback may contribute to exceptional longevity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
130
1
17

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(157 citation statements)
references
References 22 publications
(22 reference statements)
7
130
1
17
Order By: Relevance
“…Indeed, high levels of TSH (Gussekloo et al 2004) and low levels of FT4 (van den Beld et al 2005) are associated with a better survival in elderly subjects. In addition, centenarians and centenarians' offspring have higher levels of TSH compared with controls (Atzmon et al 2009a;Atzmon et al 2009b). Interestingly, thyroid failure may induce a suppression in several processes involved in nucleotide biosynthesis and DNA replication (Agocha et al 1997;Ledda-Columbano et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, high levels of TSH (Gussekloo et al 2004) and low levels of FT4 (van den Beld et al 2005) are associated with a better survival in elderly subjects. In addition, centenarians and centenarians' offspring have higher levels of TSH compared with controls (Atzmon et al 2009a;Atzmon et al 2009b). Interestingly, thyroid failure may induce a suppression in several processes involved in nucleotide biosynthesis and DNA replication (Agocha et al 1997;Ledda-Columbano et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The TSHR gene and longevity Atzmon et al (83) reported and confirmed that exceptional longevity is associated with increased serum TSH. Their further study (84) measured serum TSH and free T 4 in Ashkenazi Jewish centenarians (n ¼ 232; median age, 97 years), their offspring (n ¼ 366; median age, 69 years), and age-matched controls without familial longevity (n ¼ 163; median age, 70 years).…”
Section: The Tshr Gene and Thyroid Neoplasmsmentioning
confidence: 92%
“…This study did not resolve the question whether the decreased FT3 and TSH value observed in healthy centenarians, represents an adaptive mechanism to reduced metabolic homeostasis or a protective condition in ageing. At partial odds with these data, a population based survey and one large cross-sectional study (Atzmon et al, 2009;Surks et al, 2007) showed a progressive shift of the normal serum TSH range towards higher values from healthy young individuals up to centenarians. Overall these data seem to suggest that ageing is associated with a certain degree of down regulation of the hypothalamuspituitary-thyroid-peripheral axis, although the clinical significance of such condition is far to be elucidated.…”
Section: Thyroid Function and Ageingmentioning
confidence: 97%